Implementasi Model Pembelajaran Student Facilitator And Explaining pada Mata Pelajaran Dasar -Dasar Ketenagalistrikan - Fadila, Aisha; Usmeldi, Usmeldi (Jurnal Pendidikan Teknik Elektro, 2024)
This research aims to determine the implementation of the student facilitator and explaining learning model in the basics of electricity subject at SMK Negeri 5 Padang. It is known that many learning models have been developed by experts, but schools still use the lecture learning model. The use of inappropriate learning models results in students' lack of interest and enthusiasm in participating in the learning process so that this has an impact on low student learning outcomes. The application of the student facilitator and explaining learning model is considered to be one solution in changing the learning model which is still lecture and discussion. Therefore, it is necessary to conduct research to see the implementation of the student facilitator and explaining learning model towards improving the learning outcomes of class X TITL students at SMK Negeri 5 Padang. The type of research used is experimental research in the form of Pre Experimental Design with a One-Group Pre-test Post-test Design. The research instrument used to see changes in student learning outcomes is by giving a test in the form of objective questions consisting of 25 questions. Meanwhile, to see the success of implementing the student facilitator and explaining learning model, namely by providing a learning implementation questionnaire after implementing the learning model. The research results were analyzed using classical completeness testing, gain scores, and analysis of learning implementation for questionnaires. Based on the research results, it shows that students' grades after implementing the student facilitator and explaining learning model have increased quite significantly. Analysis of the implementation of the Student Facilitator And Explaining learning model is in the high and very high categories. Based on these data, it can be stated that the Student Facilitator And Explaining learning model is effectively used in learning the basics of electricity.